Lack of genetic variation in natural populations of a Patagonian berry with nutraceutical properties [Conjunto de datos] - Roldan, Cecilia Soledad (2022)
The file contains the folowing columns : A / ID Identifier of the sample B/ Site C/ FT Forest type (Coihue or Cypress) D:N/ diploid genotype at each microsatellite loci (2 columns per locus, -1= missing data) O / x site's coordinates , in decimal degrees P / y site's coordinates , in decimal degrees Q/ CY Collection year